Compliment Response Strategies in Institutional Discourse within an Emirati Context: Focus on Power and Gender Differences in University Student-Professor Exchanges in English - Tanju Deveci (National Research University Higher School of Economics, 2023)
Background: Context plays a significant role in effective communication. Among various aspects of context, culture is particularly important since it necessitates that language be used effectively so that a specific purpose can be achieved successfully. One key element of such communication is the effective use of speech acts including compliment and compliment responses (CR). Aim: This research aimed to identify the CR strategies produced by Emirati users of English in a university setting, as a response to a compliment received from an international professor on their academic performance and the psychological effect such a compliment is likely to have on them. It also investigated the influence of gender on CR strategies. Methodology: The data were collected using a discourse completion task. Fifty-eight students (33 male and 25 female) participated in the study. The CR strategies were analyzed using Holmes' (1988) classification scheme. Results: The results showed that a compliment from a professor, irrespective of his/her gender, would make the students happy, with positive effects on their motivation, self-confidence, and feeling of closeness to the professor. The students also thought a CR was necessary for politeness purposes. The most commonly used CR strategy was that of acceptance. The male and the female students produced similar CR strategies in responding to the professor, irrespective of his/her gender. Yet they were more likely to use micro-level strategies (e.g., appreciation token, comment, and promise) with the male professor. The students also used downgrading and disagreeing but only while responding to the male professor. In their conversation with the female professor, they used the strategies of shifting credit and requesting reassurance. Significance: These results provide evidence for the face-enhancing nature of CR strategies as utilized by Emirati users of English with international faculty in a university setting.